Criminal Responsibility towards Criminals of Abortion in Indonesia - Zahri Aeniwati; Sri Kusriyah (Law Development Journal, 2021)
This study aims to determine and describe the criminal liability of perpetrators of abortion in Indonesia. This research is a doctrinal legal research, which is descriptive analysis. The data used is secondary data obtained through library research, which is then analyzed qualitatively. The results of this research show that criminal liability for perpetrators of abortion in Indonesia based on the Criminal Code is regulated in Book Two of Chapter XIV on Crimes of Decency, especially Article 299, and Chapter XIX Articles 346-Articles 349 which are classified as crimes against life. The prohibition on abortion in the Criminal Code is contained in Article 299, Article 346, Article 347, Article 348, and Article 349, which clearly regulates the prohibition of having an abortion for any reason, including abortion for emergency reasons (forced). The provisions for regulating abortion in Act No 36 of 2009 are set forth in Article 75, Article 76, Article 77, and Article 194. Even though, the law prohibits the practice of abortion, in certain circumstances there is a possibility. Abortion practices that are contrary to statutory regulations are regulated in Article 194 of Act No 36 Of 2009, with a maximum imprisonment of 10 years and a maximum fine of IDR 1,000,000,000.00 (one billion rupiah).